IMMUNOLOGICAL ANALYSIS OF OVINE CHLAMYDIOSIS AND PATHOMORPHOLOGICAL CHANGES IN THE TISSUES OF ABORTED FETUSES - N.I, Navruzov; N.Sh, Hamroqulov; U.B, Aktamov (Research Focus International Scientific Journal, 2026)
The article presents the results of a study on optical density indicators obtained during the immunological analysis of blood serum from sheep in late pregnancy that experienced abortion due to chlamydiosis (Chlamydia abortus ovis). The study provides data on the determination of immunoglobulin classes IgG and IgM in both acute and chronic forms of Chlamydia abortus ovis infection in sheep, using diagnostic test kits produced by the joint venture “MVA GROUP” of the Republic of Kazakhstan, along with their statistical (mathematical) processing. The investigations were conducted on sheep from the “Rohat” farm in the Gallaaral district of the Jizzakh region, as well as on animals kept in private households within the same district, and in the “Turon” LLC (Karakul breeding farm) located in the Mubarek district of the Kashkadarya region. The study presents the results of immunological, serological, and pathomorphological analyses of sheep that aborted 12–14 days prior to lambing, as well as data on underdeveloped fetuses. In addition, information is provided on the pathoanatomical and histological changes observed in the internal organs of fetuses (140–150 days of gestation) that died as a result of infection with Chlamydia abortus ovis.